Salts and water‐free dyeing of cellulose nanofibers using novel green deep eutectic solvents: Isotherm, kinetics, and thermodynamic studies. Issue 23 (18th February 2022) - Mehdi, Mujahid; Hussain, Nadir; Khatri, Muzamil; Hakro, Raheel Ahmed; Ghaffar, Abdul; Khatri, Zeeshan; Kim, Ick Soo; Zhang, Ke‐Qin
Abstract: Recently, dyeing of cellulose nanofibers (CNF) has gained substantial interest due to its multifunctional properties, but discharge of hazardous effluent containing salts are biggest challenges for sustainability for textile processing sectors. Herein, we report deep eutectic solvents (DES) as a novel green dyeing medium to dye CNF with anionic reactive dyes (without salts) for the first time and dyeing parameters were optimized. Dyed CNF in DES showed 37% higher color yield compared to CNF dyed in conventional dyeing medium (with auxiliaries). The diffusion and standard affinity of both reactive dyes towards CNF in DES medium were greater than conventional (CN) medium. CNF dyed in DES revealed smooth morphology and the presence of reactive dyes confirmed by FTIR, it also offers enhanced wettability, and good color fastness properties. Therefore, DES can potentially be utilized as an effective dyeing medium. Abstract :